Antiinflammatory activity of Inula cuspidata Leaf Extract - Thapliyal, Somesh; Kumar Goel, Kapil; Goel, Nidhi (Asian Journal of Chemistry, 2010)
Inula cuspidata leaf powder was extracted with petroleum ether, chloroform, acetone, methanol and water using soxhlet apparatus. All the extracts were screened for the antiinflammatory activity by measuring the reduction in carrageenan induced hind paw edema. The potency of each extract was compared with each other and standard drug diclofenac sodium (5 mg/kg) for antiinflammatory activity. The maximum antiinflammatory activity was observed in water extract followed by petroleum ether, acetone extract, methanolic extract and chloroform extract.